2003
DOI: 10.1037/0735-7044.117.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Aggression in male mice lacking functional estrogen receptor α.

Abstract: Estrogen receptor alpha knockout (ERaKO) male mice fail to display sexual behavior. The authors hypothesized that ERalphaKOs require higher testosterone (T) concentrations than wild-type (WT) males to exhibit copulatory behavior. Increasing T stimulated sexual behavior and preference for females in WT males but failed to do so in ERalphaKOs. However, T did induce female-directed aggression in ERaKOs. In aggression tests, WT residents selectively attacked T-treated male intruders. ERaKO residents attacked femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
56
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 33 publications
5
56
0
Order By: Relevance
“…At the time of surgery each mouse received a subcutaneous SILASTIC capsule (1.02 mm inner diameter ϫ 2.16 mm outer diameter) in the midscapular region filled to 10 mm in length with crystalline testosterone (T). These implants yield plasma T levels within the physiological range for C57BL/6J males: 1-2 ng/ml (Scordalakes and Rissman, 2003). About 4 weeks later, at the end of the behavioral testing series, mice were deeply anesthetized with a lethal dose of sodium pentobarbital.…”
Section: Methodsmentioning
confidence: 99%
“…At the time of surgery each mouse received a subcutaneous SILASTIC capsule (1.02 mm inner diameter ϫ 2.16 mm outer diameter) in the midscapular region filled to 10 mm in length with crystalline testosterone (T). These implants yield plasma T levels within the physiological range for C57BL/6J males: 1-2 ng/ml (Scordalakes and Rissman, 2003). About 4 weeks later, at the end of the behavioral testing series, mice were deeply anesthetized with a lethal dose of sodium pentobarbital.…”
Section: Methodsmentioning
confidence: 99%
“…Evolutionary conserved genes affecting neurotransmitter signaling and metabolism affect aggressive behavior, including serotonin (18)(19)(20)(21)(22)(23)(24), monoamine oxidase A (25, 26), dopamine (20), octopamine (20,27), nitric oxide (28), and GABA (29). Increased aggression is associated with mutations in androgen and estrogen signaling in vertebrates (30) and sex determination in Drosophila (31,32). Genes involved in brain development or synaptogenesis have been associated with aggression in mice (33) and Drosophila (13,15,20), whereas in humans, quantitative differences in size or structure of the amygdala and prefrontal cortex have been associated with aggression (34).…”
mentioning
confidence: 99%
“…Studies of aggression (15)(16)(17) and anxiety (18) have suggested that ER␣ and ER␤ can have opposing effects on behavior, and we tested whether photoperiod regulation of receptor expression mediated the effect of photoperiod on aggression. Both ER␣ and ER␤ selective agonists increased aggression in short days but decreased aggression in long days, indicating that simple changes in receptor expression could not explain the effect of photoperiod on estrogen-mediated aggression.…”
mentioning
confidence: 99%